Efektifitas pemberian kombinasi mineral zinc dan herbal sebagai imunomodulator - Sus Derthi Widhyari; Ietje Wientarsih; Harry Soehartono; I Putu Kompiang; Wiwin Winarsih (Jurnal Ilmu Pertanian Indonesia, 2009)
Suplemen as imunomodulator used to increase immune response, to prevent disease. Herb and Zinc (Zn) can function as imunostimulan. The aim of this experiment was (1) to studythe effect of Zn mineral and herb combination influence the healthy condition, performance and immunity responses, 2) to have blood biochemistry and organ function in broiler who given zinc mineral and herb combination, 3) to know the effectivity of herb and Zn to be treated by Colibacillosis condition One hundred broiler were used in this research, divided by 5 groups: RO (control), R1 (RO + 2.5% garlic powder+ 1.5% turmeric powder), R2 (R0+2.5% garlic powder+ZnO 120ppm), R3 (R0+1.5% turmeric powder+ZnO 120ppm), R4 (R0+2.5% garlic powder +1,5% turmeric powder and ZnO 120ppm). The parameters in this research are the erythrocyte count, hemoglobin, and pack cell volume and total leucocyte. Blood biochemistry are investigate protein total, albumin, alanine aminotransferase (AL T), aspartat aminotransferase (AST), creatinin and ureum. The research showed that the erythrocyte count, hemoglobin, and pack cell and blood biochemistry in normal value, that explain safety for organ function and health group showing health status and performance is good, tested in ability to attack Colibasilosis. The result of research show and hematologi in normal, The age of chicken was 3 weeks, all of groups were treated by innoculum of Eschericia coli (E. col!) bacteria with 108 CFU.mr1 doses per-ons. The parameter was based on performance, health condition, and immunity responses. The activity and the capacity of phagositosis for assessments immunity respons, the result showed to decerease the performance and healthy condition at the first week infection, then converse to improve at the second week. The amount of leucocyt cell, especially heterophyl cell was increased at 1 week after infection as being indicated by the appearance of innoculum E. coli bacteria. The amount of leaucocyt cell was decreased directly after 2 weeks post infection at the group that was fed by turmeric-Zn (P1) and gave antibiotic (K+) drug. This condition showed that the body defence fastly to eliminate the infected agent which was supported by increasing phagocyitosis capacity (327±111 bacteria) and phagocyitosis activity 97%±10%, was compared with the control group (without drug) activity value 85±15% and phagocytosis capacity (176±118 bacteria). Feeding by turmeric-Zn combination showed better result which was compared to Garlic-Zn combination and the ability to increase healthy condition, performance and immunuity responses.